(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2018)
The main purpose of this research was to identify 4 to 6-year-old children’s ideas about microorganisms, taking into consideration the learning processes carried out in different educational contexts. To this end, data were collected from two institutions – a science museum and a kindergarten – by means of interviews, recorded conversations, drawings, and the application of a didactic sequence with the kindergarten group. A qualitative analysis of the data revealed that children associate the presence of microorganisms with dirty places and see them as pathological agents. The children demonstrated that they understand the idea of scale and the need for magnifying instruments. We found that they consider microorganisms morphologically similar to insects and that they use various scientific words appropriately. It was concluded that young children understand the theme “microorganisms”, and that it should be addressed more actively by institutions that teach four- to six-year-olds, which are responsible for contributing to their scientific literacy and science learning in childhood. It is proposed that the following themes be developed in educational activities with young children: biodiversity, scale, biological functions, and relationships with humans and food.